1999
DOI: 10.1111/j.1469-7793.1999.0835u.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of PI3‐kinase in the development of interstitial cells and pacemaking in murine gastrointestinal smooth muscle

Abstract: Development of the pacemaker system in the small intestine depends upon signalling via tyrosine kinase (Kit) receptors. The downstream pathways initiated by Kit in interstitial cells of Cajal (ICC) have not been investigated. Wortmannin and 2‐(4‐morpholinyl)‐8‐phenyl‐4H‐1‐benzopyran‐4‐one (LY 294002), inhibitors of phosphatidylinositol 3′‐kinase (PI3‐kinase), were used to test the involvement of this pathway in the development and maintenance of ICC and electrical rhythmicity in the murine small intestine. ICC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
(51 reference statements)
2
21
2
1
Order By: Relevance
“…These data demonstrate the extensive plasticity of ICC in the gastrointestinal tract. We have previously shown that Kit neutralization can inhibit pacemaker activity in jejunal tissues from P10 animals, but the time required to block slow waves (35 days) was much longer than that required to block activity in P0 muscles (the present study), suggesting the sensitivity of ICC to signaling via the Kit receptor varies as a function of the developmental period of the animal (Ward et al,1999).…”
Section: Discussioncontrasting
confidence: 50%
“…These data demonstrate the extensive plasticity of ICC in the gastrointestinal tract. We have previously shown that Kit neutralization can inhibit pacemaker activity in jejunal tissues from P10 animals, but the time required to block slow waves (35 days) was much longer than that required to block activity in P0 muscles (the present study), suggesting the sensitivity of ICC to signaling via the Kit receptor varies as a function of the developmental period of the animal (Ward et al,1999).…”
Section: Discussioncontrasting
confidence: 50%
“…Intestinal preparations taken from mutant mice that lack myenteric ICC failed to generate slow waves, although they can generate action potentials (20,35). Similar findings were obtained from preparations in which the development of ICC was impaired with an antibody to c-kit, a component of ICC (25,34,37).…”
supporting
confidence: 59%
“…Similar results were reported previously that the signal pathway was essential for development of the ICCs during the fetal and neonatal periods (Maeda et al,1992; Kluppel et al,1998). In vitro study also showed that blockade of Kit or its downstream, PI3‐kinase, led to a reduction of ICCs in the bowel organ cultures from the adult mice (Ward et al,1999).…”
Section: Discussionmentioning
confidence: 99%